Inhaled sGC Modulator Can Lower PH in Patients With COPD Without Deteriorating Oxygenation. (2nd July 2018) - Saffaran, Sina; Wang, Wenfei; Das, Anup; Schmitt, Walter; Becker‐Pelster, Eva‐Maria; Hardman, Jonathan G.; Weimann, Gerrit; Bates, Declan G.
Abstract : This study uses a highly fidelity computational simulator of pulmonary physiology to evaluate the impact of a soluble guanylate cyclase (sGC) modulator on gas exchange in patients with chronic obstructive pulmonary disease (COPD) and pulmonary hypertension (PH) as a complication. Three virtual patients with COPD were configured in the simulator based on clinical data. In agreement with previous clinical studies, modeling systemic application of an sGC modulator results in reduced partial pressure of oxygen (PaO2 ) and increased partial pressure of carbon dioxide (PaCO2 ) in arterial blood, if a drug‐induced reduction of pulmonary vascular resistance (PVR) equal to that observed experimentally is assumed. In contrast, for administration via dry powder inhalation (DPI), our simulations suggest that the treatment results in no deterioration in oxygenation. For patients under exercise, DPI administration lowers PH, whereas oxygenation is improved with respect to baseline values.